Pengaruh Rekayasa Tingkat Energi Routing Protocol Dynamic Source Routing (DSR) pada Mobile Ad Hoc Network (MANET) - Hilmy Riadika; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
A Mobile Ad Hoc Network (MANET) is a network consisting of multiple nodes that are interconnected to exchange data. Nodes act as routers to route packets to other nodes. A routing protocol is needed to exchange data. Dynamic Source Routing (DSR) is an example of a reactive routing protocol often used in MANETs. Nodes in a MANET have limited energy, so energy conservation is necessary. One method for conserving energy in nodes is by engineering the energy level and by selecting the appropriate routing protocol, such as the DSR protocol. This research uses two testing scenarios: one with energy conservation and one without. The parameters used are packet delivery ratio (PDR) and remaining energy. The results show that the scenario without energy conservation performs better in improving system performance with the DSR routing protocol. Optimal energy use can improve system performance with the DSR routing protocol because it ensures that there are enough nodes with sufficient energy to continue sending and receiving packets. This will increase the packet delivery ratio (PDR) because more messages are successfully sent and received. On the other hand, if energy use is not optimal, then there will be more nodes that run out of energy before all messages can be sent and received, resulting in a lower packet delivery ratio (PDR).